Effect of physical activity through virtual reality on design creativity. Issue 1 (21st February 2021) - Fillingim, Kenton B.; Shapiro, Hannah; Reichling, Catherine J.; Fu, Katherine
Abstract: A deeper understanding of creativity and design is essential for the development of tools to improve designers' creative processes and drive future innovation. The objective of this research is to evaluate the effect of physical activity versus movement in a virtual environment on the creative output of industrial design students. This study contributes a novel assessment of whether the use of virtual reality can produce the same creative output within designers as physical activity has been shown to produce in prior studies. Eighteen industrial design students at the Georgia Institute of Technology completed nine design tasks across three conditions in a within-subjects experimental design. In each condition, participants independently experienced one of three interventions. Solutions were scored for novelty and feasibility, and self-reported mood data was correlated with performance. No significant differences were found in novelty or feasibility of solutions across the conditions. However, there are statistically significant correlations between mood, interventions, and peak performance to be discussed. The results show that participants who experienced movement in virtual reality prior to problem solving performed at an equal or higher level than physical walking for all design tasks and all designer moods. This serves as motivation for continuing to study how VR can provide an impact on a designer's creative output. Hypothesized creative performance with each mode is discussed using trends from four categories of mood, based on the combined mood characteristics of pleasantness (positive/negative) and activation (active/passive).